2005
DOI: 10.2337/diabetes.54.11.3103
|View full text |Cite
|
Sign up to set email alerts
|

Glycation and Carboxymethyllysine Levels in Skin Collagen Predict the Risk of Future 10-Year Progression of Diabetic Retinopathy and Nephropathy in the Diabetes Control and Complications Trial and Epidemiology of Diabetes Interventions and Complications Participants With Type 1 Diabetes

Abstract: Several mechanistic pathways linking hyperglycemia to diabetes complications, including glycation of proteins and formation of advanced glycation end products (AGEs), have been proposed. We investigated the hypothesis that skin collagen glycation and AGEs predict the risk of progression of microvascular disease. We measured glycation products in the skin collagen of 211 Diabetes Control and Complications Trial (DCCT) volunteers in 1992 who continued to be followed in the Epidemiology of Diabetes Interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
312
2
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(327 citation statements)
references
References 49 publications
6
312
2
7
Order By: Relevance
“…The data support the assumption that the formation of collagen FL is in equilibrium with ambient glucose concentrations [5]. Glycation alone may have a pathogenic role in the development of diabetic complications, and collagen FL is a predictor of complications in DCCT subjects [21,22].…”
Section: Collagen Glycation Glycaemic Control and Complicationssupporting
confidence: 69%
See 1 more Smart Citation
“…The data support the assumption that the formation of collagen FL is in equilibrium with ambient glucose concentrations [5]. Glycation alone may have a pathogenic role in the development of diabetic complications, and collagen FL is a predictor of complications in DCCT subjects [21,22].…”
Section: Collagen Glycation Glycaemic Control and Complicationssupporting
confidence: 69%
“…The data support the contention that 4 years is a sufficient period of time for equilibration even of the end-products. Given that the recent DCCT report shows that the skin collagen FL and CML levels measured earlier (in 1991-1992) predict the 10-year incidence of retinopathy and nephropathy during EDIC [22], the combination of observations adds further support to the idea that damage resulting from glycation and CML formation may have long-term downstream effects that may explain the 'memory effect' of intensive treatment found during the DCCT.…”
Section: Ages Metso and Complicationsmentioning
confidence: 66%
“…An increase in skin AGEs can predict progression of diabetic retinopathy and nephropathy in type 1 diabetes [28]. Compared with the use of samples from skin biopsies for measurement of AGEs, serum samples are simple, and with standardisation they could become a useful clinical tool.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue glycation and/or oxidation via intra-and extracellular generation of AGEs may promote diabetes complications. The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/ EDIC) demonstrated in skin biopsies that collagen AGEs predict microvascular disease (12). Skin collagen methionine sulfoxide, a marker of oxidative damage independent of glycemia, has also been associated with type 1 diabetes complications (13).…”
Section: Discussionmentioning
confidence: 99%